The Impact of Tourism on Community Food Security in Berastagi, Karo Regency - Auziva, Vania; Rokan, Mustafa Kamal; Hasibuan, Faisal Umardani (Amkop Management Accounting Review (AMAR), 2026)
As one of the main tourist destinations in North Sumatra Province, Berastagi is not only known for its natural and cultural tourism potential, but also as a center for horticultural agriculture, which is a major pillar of local food security. Therefore, research is needed regarding the impact of tourism on community food security in Berastagi, Karo Regency. This study aims to analyze the impact of tourism on community food security in Berastagi, Karo Regency. This study uses a qualitative approach by conducting in-depth interviews with farmers and traders, accompanied by secondary data analysis regarding the development of the tourism sector and agricultural conditions. The results of this study indicate that the impact of tourism provides opportunities to increase community income. However, these benefits are not evenly distributed, seen as challenges arise such as food prices becoming very expensive, food supplies are unstable due to reduced agricultural land, food production is disrupted by climate change and extreme weather, and household economies become very vulnerable during the low season. Thus, this study confirms that tourism has a dual impact on the food security of the Berastagi community, so that sustainable management strategies are needed so that the tourism and agricultural sectors can support each other.